Candide, La fée carabine et les autres. Vers un modèle didactique de la lecture littéraire - Aeby Daghé, Sandrine (Peter Lang International Academic Publishers, 2021)
How do teachers read Voltaire's Candide and The Pennac rifle fairy with 16 year-old students? Beyond the different effects related to the length and status of texts, this book shows that teachers use school activities to read literary texts and ensure links with the readings of the students.